Monetary Risk and Market Dynamics as Drivers of Capital Market Deepening in ASEAN: A Sustainable Development Perspective - Yohanes Joni Pambelum; Ronni Haga; Sunaryo Neneng (Universitas Bangka Belitung, 2026)
This study investigates the drivers of capital market deepening in ASEAN countries from a sustainable development perspective. It focuses on the influence of stock market returns, GDP growth rate, inflation rate, and IPO activity on the market capitalization-to-GDP ratio. Using a panel dataset covering six ASEAN countries from 2010 to 2024, the study applies the System Generalized Method of Moments (System GMM) to account for endogeneity and dynamic effects. The results reveal that stock market returns and inflation rate have a significant positive impact on capital market deepening, while GDP growth rate and IPO count do not show significant effects. These findings highlight the importance of financial market performance and monetary conditions in enhancing financial depth in emerging markets. The study offers valuable insights for policymakers aiming to strengthen capital markets as a means of supporting inclusive and sustainable economic development in the ASEAN region.